Can models of organizational change help to understand 'success' and 'failure' in community sentences? Applying Kotter's model of organizational change to an Integrated Offender Management case study. (July 2018) - King, Sam; Hopkins, Matt; Cornish, Neil
A number of nationally driven initiatives have led to significant changes in the framework of community sentences, with various agencies being required to work in 'joined-up' multi-agency arrangements. Most notable, perhaps, has been the increased working relationship between police and probation, most recently within Integrated Offender Management (IOM). Although these have produced some positive outcomes in relation to crime reduction, success is sporadic and often quite modest. Research has identified a number of barriers to successful implementation, and this article builds on this by drawing upon fresh empirical evidence to argue that the success of such schemes relies on the management of organizational change that will inevitably and necessarily occur. Applying Kotter's model of organizational change to data generated from an evaluation of two IOM schemes in England, the article offers an explanatory account of the implementation of the schemes and the possible effect this had on efforts to reduce crime.